Treatment decision-making among breast cancer patients in Malaysia - Nies, Yong Hui (Patient Prefer Adherence, 2017)
PURPOSE: This study investigated breast cancer patients’ involvement level in the treatment decision-making process and the concordance between patients’ and physician’s perspectives in decision-making. PARTICIPANTS AND METHODS: A cross-sectional study was conducted involving physicians and newly diagnosed breast cancer patients from three public/teaching hospitals in Malaysia. The Control Preference Scale (CPS) was administered to patients and physicians, and the Krantz Health Opinion Survey (KHOS) was completed by the patients alone. Binary logistic regression was used to determine the association between sociodemographic characteristics, the patients’ involvement in treatment decision-making, and patients’ preference for behavioral involvement and information related to their disease. RESULTS: The majority of patients preferred to share decision-making with their physicians (47.5%), while the second largest group preferred being passive (42.6%) and a small number preferred being active (9.8%). However, the physicians perceived that the majority of patients preferred active decision-making (56.9%), followed by those who desired shared decision-making (32.8%), and those who preferred passive decision-making (10.3%). The overall concordance was 26.5% (54 of 204 patient–physician dyads). The median of preference for information score and behavioral involvement score was 4 (interquartile range [IQR] =3–5) and 2 (IQR =2–3), respectively. In univariate analysis, the ethnicity and educational qualification of patients were significantly associated with the patients’ preferred role in the process of treatment decision-making and the patients’ preference for information seeking (p>0.05). However, only educational qualification (p=0.004) was significantly associated with patients’ preference for information seeking in multivariate analysis. CONCLUSION: Physicians failed to understand patients’ perspectives and preferences in treatment decision-making. The concordance between physicians’ perception and patients’ perception was quite low as the physicians perceived that more than half of the patients were active in treatment decision-making. In actuality, more than half of patients perceived that they shared decision-making with their physicians.